Identification of Object Dynamics Using Hand Worn Motion and Force Sensors - Henk G. Kortier; H. Martin Schepers; Peter H. Veltink (Sensors, 2016)
Emerging microelectromechanical system (MEMS)-based sensors become much more applicable for on-body measurement purposes lately. Especially, the development of a finger tip-sized tri-axial force sensor gives the opportunity to measure interaction forces between the human hand and environmental objects. We have developed a new prototype device that allows simultaneous 3D force and movement measurements at the finger and thumb tips. The combination of interaction forces and movements makes it possible to identify the dynamical characteristics of the object being handled by the hand. With this device attached to the hand, a subject manipulated mass and spring objects under varying conditions. We were able to identify and estimate the weight of two physical mass objects (0.44 kg: 29 . 3 % ± 18 . 9 % and 0.28 kg: 19 . 7 % ± 10 . 6 % ) and the spring constant of a physical spring object ( 16 . 3 % ± 12 . 6 % ). The system is a first attempt to quantify the interactions of the hand with the environment and has many potential applications in rehabilitation, ergonomics and sports.